Preparation, in vitro and in vivo evaluation of a novel mitiglinide microemulsions - Miaomiao Wang; Hanghang Li; Wenzhi Yang (Elsevier, 2024)
This study aimed to prepare an o/w mitiglinide microemulsion (MTGME) to improve the drug solubility and bioavailability. The formulation of o/w MTGME was optimized by the solubility study of drug, pseudo-ternary phase diagram and Box-Behnken design successively. MTGME was characterized by dynamic laser light scattering (DLS), zeta potential and transmission electron microscopy (TEM), moreover, the storage stability, pharmacodynamics and pharmacokinetics were investigated. The optimal prescription for MTGME consisted of Maisine 35-1 (oil), Cremophor EL (surfactant) and propylene glycol (PG, cosurfactant). MTGME with a spherical dimension of 58.1 ± 5.86 nm was stable when stored at 4 °C for 3 months. The blood glucose levers (BGL) of diabetic mice were uniformly and significantly decreased by intragastric (i.g.) administration of 1-4 mg/kg MTGME, in which BGL (i.g. 4 mg/kg MTGME) was reduced by 69% during 24 h. The pharmacokinetics study of MTGME (i.g., 20 mg/kg) in Wistar rats showed higher plasma drug concentration (Cmax, 2.9 folds), larger area under curve (AUC, 4.6 folds) and oral bioavailability than those of MTG suspensions. Generally, the MTGME (o/w) showed good effect on controlling hyperglycemia. Therefore, microemulsion can be used as an effective oral drug delivery system to improve the bioavailability of MTG.